Hypophyseal and gonadal response of late maturing Murrah buffalo heifers (Bubaius bubalis) receiving GnRH, PGF2α and eCG - SINGH, C; MADAN, M L (The Indian Journal of Animal Sciences, 2014)
The pattern of hypophyseal and gonadal hormone release and gonadal potential in terms of follieulogenesis and ovulation was studied in 4 late maturing Murrah buffalo heifers. They were injected with 200 µg of GnRH intravenously at 42 months of age (day 0), PGFp intramuscularly on day 45 (30 mg) and day 57 (25 mg). cCG (2500 IU.IM) on day 55 and GnRH (200 µg, iv) at induced estrus on day 59. Blood samples were collected via jugular catheter for estimation of hormones. The pretreatment plasma estradiol, progesterone. FSH and LH concentration were 7.64 ± 1.69 pg/mL 0.20 ± 0.04 ng/ml. 9.22 ± 1.50 ng/ml and 0.63 ± 0.04 ng/ml, rcspectively, on day 0. Estradiol concentration increased to 20.76 ± 1.10 pg/ml on day 13. All heifers wcre detected in estrus between days 25 and 35. The eCG adminbLration (day 55) induced multiple follicular development and estrus on day 59. Total number (mean ± SE) of palpable follicles and ovulation at induced estrus (day 59) were, respectively, 4.00 ± 0.00 and 2.25 ± 0.25. GnRH injection triggered significantly (P